Kenduri Dalam Perspektif Pendidikan Islam - Sari Haryati; Jarir; Nuratika; Syafei (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the practice of kenduri from the perspective of Islamic education, focusing on its role in transmitting religious values and shaping moral character within Muslim communities in the Indonesian archipelago. The study employs a qualitative approach with a case study design, utilizing observation, interviews, and document analysis to explore how kenduri functions as a non-formal educational medium. The findings indicate that kenduri is not merely a social and religious ritual but a dynamic practice that embodies key Islamic educational values, including monotheism, gratitude, brotherhood, ta'awun (mutual assistance), and moral development. Through communal prayers, charitable activities, and collective preparation of feasts, participants internalize spiritual and social values experientially, fostering sincerity, humility, togetherness, and social awareness. Moreover, kenduri strengthens social cohesion and enhances divine consciousness by integrating cognitive, affective, and psychomotor aspects of learning within a communal context. These results highlight the relevance of kenduri as an effective contextualized educational strategy for contemporary Islamic education, demonstrating its potential to build moral society, reinforce Islamic identity, and cultivate character formation in daily life.